THE CORRELATION AMONG ATTITUDE, MOTIVATION AND SPEAKING ACHIEVEMENT OF COLLEGE STUDENTS ACROSS PERSONALITY FACTORS - Siti Lailatul Khoiriyah (OKARA: Jurnal Bahasa dan Sastra, 2016)
Considering the important of understanding about the attitude, motivation and the personality of the students in the English learning process, this research is aimed at finding the relationship between attitude and motivation which are acknowledged as influential factors in speaking achievement across their personality factors. Sixty Non-EFL students of Maulana Malik Ibrahim State Islamic University of Malang who take English as their compulsory subject were participated as the research sample. They were the fourth semester undergraduate taking TOEFL and Speaking Course. Attitude and Motivation Test Battery (AMTB), The Myers-Briggs Type Indicator (MBTI), speaking test and TOEFL-like test were administered. The results of this research revealed that there was significant correlation among attitude, motivation and speaking achievement of extrovert and Introvert students.